Molecular pathways of senescence regulate placental structure and function. (19th August 2019) - Gal, Hilah; Lysenko, Marina; Stroganov, Sima; Vadai, Ezra; Youssef, Sameh A; Tzadikevitch‐Geffen, Keren; Rotkopf, Ron; Biron‐Shental, Tal; de Bruin, Alain; Neeman, Michal; Krizhanovsky, Valery
Abstract: The placenta is an autonomous organ that maintains fetal growth and development. Its multinucleated syncytiotrophoblast layer, providing fetal nourishment during gestation, exhibits characteristics of cellular senescence. We show that in human placentas from pregnancies with intrauterine growth restriction, these characteristics are decreased. To elucidate the functions of pathways regulating senescence in syncytiotrophoblast, we used dynamic contrast‐enhanced MRI in mice with attenuated senescence programs. This approach revealed an altered dynamics in placentas of p53 −/−, Cdkn2a −/−, and Cdkn2a −/− ; p53 −/− mice, accompanied by histopathological changes in placental labyrinths. Human primary syncytiotrophoblast upregulated senescence markers and molecular pathways associated with cell‐cycle inhibition and senescence‐associated secretory phenotype. The pathways and components of the secretory phenotype were compromised in mouse placentas with attenuated senescence and in human placentas from pregnancies with intrauterine growth restriction. We propose that molecular mediators of senescence regulate placental structure and function, through both cell‐autonomous and non‐autonomous mechanisms. Synopsis: Intrauterine growth restriction is among the most frequent pregnancy complications associated with abnormalities in placental growth, structure and function, and is a major cause of fetal morbidity and mortality. This study links compromised cellular senescence to pathophysiology of intrauterine growth restriction. Human placentas from pregnancies with intrauterine growth restriction exhibit reduced activity of senescence pathways and gelatinase activity. Dynamic contrast‐enhanced MRI reveals that mice deficient for senescence pathways have reduced placental function. Senescence‐deficient mice display morphological aberrations in placental labyrinths. Genome‐wide transcriptional analyses reveal that human placental syncytiotrophoblast upregulate expression of genes associated with senescence‐regulatory pathways and senescence‐associated secretory phenotype (SASP) during cytotrophoblast differentiation in culture. Reduced senescence and SASP is accompanied by diminished gelatinase activity in mouse and human placentas. Abstract : Compromised cellular senescence in the multinucleated syncytiotrophoblast layer is associated with pathophysiology of intrauterine growth restriction during pregnancy in mice and humans.